2011
DOI: 10.1042/bj20101734
|View full text |Cite
|
Sign up to set email alerts
|

WT1 and its transcriptional cofactor BASP1 redirect the differentiation pathway of an established blood cell line

Abstract: The Wilms' tumour suppressor WT1 (Wilms' tumour 1) is a transcriptional regulator that plays a central role in organogenesis, and is mutated or aberrantly expressed in several childhood and adult malignancies. We previously identified BASP1 (brain acid-soluble protein 1) as a WT1 cofactor that suppresses the transcriptional activation function of WT1. In the present study we have analysed the dynamic between WT1 and BASP1 in the regulation of gene expression in myelogenous leukaemia K562 cells. Our findings re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 43 publications
10
56
0
Order By: Relevance
“…6d) (Rege and Hagood, 2006), and INA (FC 89) (Baum and Garriga, 1997). Additional down-regulated genes were involved in neuron differentiation and stabilization such as FERD3L (FC 104) (Ono et al , 2010), BASP1 (FC 200) (Goodfellow et al , 2011), and HSPA12B (FC 119) (Ono et al , 2010). Finally, other highly down-regulated genes played a role in cell proliferation ( MZF1 , FC 124) (Gaboli et al , 2001); DNA damage repair ( XRCC3 , FC 121) (Kurumizaka et al , 2001); and protein transport ( SSR4 , FC 183) (Nagasawa et al , 2007) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6d) (Rege and Hagood, 2006), and INA (FC 89) (Baum and Garriga, 1997). Additional down-regulated genes were involved in neuron differentiation and stabilization such as FERD3L (FC 104) (Ono et al , 2010), BASP1 (FC 200) (Goodfellow et al , 2011), and HSPA12B (FC 119) (Ono et al , 2010). Finally, other highly down-regulated genes played a role in cell proliferation ( MZF1 , FC 124) (Gaboli et al , 2001); DNA damage repair ( XRCC3 , FC 121) (Kurumizaka et al , 2001); and protein transport ( SSR4 , FC 183) (Nagasawa et al , 2007) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several of these (BASP1/MARCKS/MARCKSL1) interact, and although not known as direct interactors of β-catenin, may function (or interact) in concert with β-catenin as shown in Figure 6. BASP1 is a well-characterized interactor of WT1/Wilms Tumor 1, functioning as a transcriptional cosuppressor (38,39). For example, FAM123B/WTX (Wilms tumor on the X) is a WT1 associated protein, that also directly interacts with APC and β-catenin (40,41).…”
Section: Resultsmentioning
confidence: 99%
“…We note, however, that LEF1 expression is not evident in all the regions of the placode that express WT1, suggesting that other factors are also important. Indeed, we and others have previously shown that the function of WT1 in transcriptional activation is modulated by its interaction with BASP1 and that this is both cell type-and gene promoter-specific (Essafi et al, 2011;Goodfellow et al, 2011;Green et al, 2009). It will therefore be important to study the potential role of BASP1 in modulating WT1 function during CV formation.…”
Section: Discussionmentioning
confidence: 99%